EKSPERIMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING, SNOW BALLING, DAN PROBLEM BASED LEARNING DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI GAYA BELAJAR SISWA SMP SWASTA DI KABUPATEN PONOROGO TAHUN PELAJARAN 2014/2015 - Ahmad Husni Mubarok; Tri Atmojo Kusmayadi; Imam Sujadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purpose of this research was to investigate the impact of the learning model toward student’s mathematics achievement seen from student’s learning style. The learning models compared were Discovery Learning, Snow Balling and Problem Based Learning using scientific approach (DL-S, SB-S, and PBL-S). This research was the quasi experimental with factorial design 3x3. The populations of this research was students at eight grade of private Junior High school in Ponorogo in the academic year of 2014/2015. The size of the sample was 336 students, consisted of 115 students in the first experimental group, 107 students in second experimental group and 114 students in third experimental group. The instruments consisted of learning achievement test and questionnaire of learning style. Hypotheses testing was performed using two-way analysis of variance with unbalanced cells. The results of the research were. (1) Learning achievement using DL-S learning model is better than that of SB-S, learning achievement using DL-S learning model is better than that of PBL-S, SB-S and PBL-S learning model have the same achievement. (2) Visual students have better mathematics achievement than auditory and kinesthetic students, auditory and kinesthetic students have the same achievement (3) In visual, auditory, and kinesthetics students, DL-S have better achievement than SB-S and PBL-S, SB-S and PBL-S have the same achievement. (4) In DL-S, SB-S, and PBLS, visual and auditory students have better achievement than kinesthetics students, auditory and kinesthetics students have the same achievement.Keywords: scientific approach, DL-S, SB-S, PBL-S learning, learning style, learning achievement